2012
DOI: 10.1007/s10096-012-1805-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-diphtheriae Corynebacterium species: an emerging respiratory pathogen

Abstract: The purpose of the study was to describe the microbiological and clinical features of ten cases of lower respiratory tract infection due to Corynebacterium striatum, Corynebacterium propinquum and Corynebacterium pseudodiphtheriticum. Respiratory samples were recovered from hospitalised patients who were diagnosed of pneumonia and exacerbations of chronic respiratory infections. The samples were Gram-stained and seeded on conventional bacterial growing media. Bacteria were identified by matrix-assisted linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 16 publications
0
42
1
7
Order By: Relevance
“…These results indicated that GPB, such as streptococci and Corynebacterium species, and anaerobes should be considered in addition to GNB in the pathogenesis of HAP. The predominant phylotypes of Corynebacterium species were commonly detected (11.8%) compared to the previous report in this study (Enne et al 2014), but the pathogenesis of Corynebacterium species (other than Corynebacterium pseudodiphtheriticum) in patients with pneumonia remains controversial (Renom et al 2007;Nhan et al 2012;Díez-Aguilar et al 2013). We previously reported that a total bacterial cell count of > 10 4 cells/mL in BALF specimens is a useful criterion for diagnosing respiratory bacterial infection (Yamasaki et al 2013), and all cases with positive PCR results fulfilled this criterion in the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…These results indicated that GPB, such as streptococci and Corynebacterium species, and anaerobes should be considered in addition to GNB in the pathogenesis of HAP. The predominant phylotypes of Corynebacterium species were commonly detected (11.8%) compared to the previous report in this study (Enne et al 2014), but the pathogenesis of Corynebacterium species (other than Corynebacterium pseudodiphtheriticum) in patients with pneumonia remains controversial (Renom et al 2007;Nhan et al 2012;Díez-Aguilar et al 2013). We previously reported that a total bacterial cell count of > 10 4 cells/mL in BALF specimens is a useful criterion for diagnosing respiratory bacterial infection (Yamasaki et al 2013), and all cases with positive PCR results fulfilled this criterion in the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…Corynebacterium spp. are uncommon but well-documented causes of respiratory infection (20), and our findings raise the possibility that they and other pharynx-associated microbes may be underappreciated as respiratory pathogens due to occasional misdesignation as oral flora in respiratory cultures.…”
Section: Figmentioning
confidence: 70%
“…MALDI-TOF MS was also utilized as the primary mechanism for definitive species-level identification of uncommonly encountered corynebacterial isolates (135). As databases become better populated and more refined, studies such as these will play an important role in both pathogen detection and the identification of novel emerging pathogens, particularly for groups of often overlooked organisms, such as the corynebacteria.…”
Section: Corynebacterium Sppmentioning
confidence: 99%